2012
DOI: 10.1042/bj20120675
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte storage increases rates of NO and nitrite scavenging: implications for transfusion-related toxicity

Abstract: Synopsis Storage of erythrocytes in blood banks is associated with biochemical and morphological changes to the RBC. It has been suggested that these changes have a potential negative clinical effects characterized by inflammation and microcirculatory dysfunction which add to other transfusion related toxicities. However, mechanisms linking RBC storage and toxicity remain unclear. In this study we tested the hypothesis that storage of leukodepleted RBC result in cells that inhibit nitric oxide (NO)-signaling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 51 publications
1
68
1
Order By: Relevance
“…This suggests that approximately 15% of the measured plasma hemoglobin in the current study is contained in microparticles. Similarly, Stapley and colleagues (21) demonstrated that microparticle levels increased during red cell storage, with the highest levels measured at 42 days of storage. Kinetic modeling demonstrated that there was a 40-fold increase in red cell-dependent NO scavenging with 42-day blood compared with fresh blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that approximately 15% of the measured plasma hemoglobin in the current study is contained in microparticles. Similarly, Stapley and colleagues (21) demonstrated that microparticle levels increased during red cell storage, with the highest levels measured at 42 days of storage. Kinetic modeling demonstrated that there was a 40-fold increase in red cell-dependent NO scavenging with 42-day blood compared with fresh blood.…”
Section: Discussionmentioning
confidence: 99%
“…However, in these studies the mean ages of older blood were only 22 and 28.3 days, respectively, and very few units of blood were transfused at the extreme limits of FDA-approved storage of 42 days (16)(17)(18). Thus, although transfusion of blood may increase risk (12,13,15,19), whether this risk is compounded by storage age, especially at the limits of storage and in the setting of larger transfusion volumes, remains unclear (20)(21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Stored RBCs have been described to lose blebs of membrane during storage. 25 Accordingly, EV counts rose by day 42 of storage ( Figure 1C). Annexin-V reactivity of EVs was 15% to 35% and was dependent on the concentration of Ca 11 (data not shown); however, 89% of EVs were reactive with lactadherin at 3 time points ( Figure 1D).…”
Section: Characterization Of Evs In Stored Rbc Unitsmentioning
confidence: 98%
“…In addition, recent studies show that the effects of storage will lead to an increased intrinsic NO scavenging by older stored RBCs, as measured by nitric oxide competition experiments and inhibition of aortic vasodilation [20,43,44]. However, the extent of the increase in NO scavenging by older red blood cells compared to fresh ones was not fully explored and the mechanism for this phenomenon was not satisfactorily provided.…”
Section: Introductionmentioning
confidence: 99%
“…These changes result in a reduced deformability, increased osmotic fragility, spheroechinocyte formation, reduced integrity of the erythrocyte membrane with Abbreviations: NO, nitric oxide; RBC, red blood cell; Hb, hemoglobin; MCHC, mean corpuscular hemoglobin concentration; MCV, mean corpuscular hemoglobin volume; PBS, phosphate buffered saline; MetHb, methemoglobin formation of microparticles, and increased cell-free hemoglobin (Hb) in plasma [11][12][13][14][15][16][17]. Numerous studies have found that the geometry of the red blood cell tends to become more spherical during storage thereby having a smaller surface area to volume ratio [10,[18][19][20]. The mean corpuscular hemoglobin concentration decreases, and the structure of RBC membrane changes significantly during storage [21,22].…”
Section: Introductionmentioning
confidence: 99%